Immune Checkpoint Inhibitors for Hepatocellular Carcinoma - Dika, Imane El (Cancer, 2019)
The position of immunotherapy as a pillar of systemic cancer treatment has been firmly established over the past decade. Immune checkpoint inhibitors are a welcome option for patients with different malignancies. This is in part because they offer the possibility of durable benefit, even for patients who have failed other treatment modalities. The recent demonstration that immunotherapy is effective for patients with hepatocellular carcinoma (HCC) is a milestone in the history of this recalcitrant disease. The treatment of HCC has been a challenge, and for many years was limited to the tyrosine kinase inhibitor sorafenib and to several novel tyrosine kinase inhibitors that have shown efficacy and have been approved. The current role of immune checkpoint inhibitors in the management of HCC, and how this role is likely to evolve in the years ahead, are key. Other than efforts evaluating single checkpoint inhibitors, potential combination strategies, including combinations with existing local and systemic approaches, including novel therapies are evolving. This is understandably of special interest considering the potential unique immune system of the liver, which may impact the use of immunotherapy in patients with HCC going forward, and how can it be enhanced further.